Editorial: A wonder legume, soybean: prospects for improvement - Ramlal, A.; Nautiyal, A.; Lal, S.K.; Chigeza, G. (Frontiers Media, 2023)
*Glycine max* (L.) Merr. (soybean) is an economically, agriculturally and industrially (food, paper, textile, pharmaceuticals) important crop on a global scale. It is often referred to as a 'wonder legume' and 'gold from the soil' due to its substantial value and versatile nature. Soybean seeds are rich in proteins and serve as a vital source of macronutrients, micronutrients, vitamins, and minerals. It holds a crucial role as a multi-purpose crop, serving both as animal feed and as a staple in human diets ([Song et al., 2023](https://www.frontiersin.org/journals/plant-science/articles/10.3389/fpls.2023.1294185/full#B12)). Soybean is also a medicinal crop and harbours diverse compounds known for their therapeutic potential ([Ramlal et al., 2022a](https://www.frontiersin.org/journals/plant-science/articles/10.3389/fpls.2023.1294185/full#B9); [Ramlal et al., 2023a](https://www.frontiersin.org/journals/plant-science/articles/10.3389/fpls.2023.1294185/full#B8)). Traditionally, soybean has been cultivated using conventional breeding methods, driven by the necessity to enhance production to meet the growing population's demands which is a time-consuming and tedious process ([Maranna et al., 2016](https://www.frontiersin.org/journals/plant-science/articles/10.3389/fpls.2023.1294185/full#B5)). Breeding endeavours also focus on elevating the quality of proteins and oils while concurrently reducing anti-nutritional components.